2016
DOI: 10.1002/hbm.23445
|View full text |Cite
|
Sign up to set email alerts
|

Similarities and differences in the default mode network across rest, retrieval, and future imagining

Abstract: The default mode network (DMN) has been identified reliably during rest, as well as during the performance of tasks such as episodic retrieval and future imagining. It remains unclear why this network is engaged across these seemingly distinct conditions, though many hypotheses have been proposed to account for these effects. Prior to generating hypotheses explaining common DMN involvement, the degree of commonality in the DMN across these conditions, within individuals, must be statistically determined to tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
66
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(74 citation statements)
references
References 108 publications
(179 reference statements)
7
66
1
Order By: Relevance
“…Different cognitive processes also influence both the activation and connectivity of the DMN during resting-state scanning (Bellana, et al, 2017; Benjamin, et al, 2010; Chou, et al, 2017; Demertzi, et al, 2011; Van Calster, et al, 2016; Yan, et al, 2009). Although task-based fMRI has indicated that DMN regions increase in activity for episodic memory and internally driven mentalizing tasks (Buckner, et al, 2008), our findings suggest that relatively long bouts of minimally guided autobiographical retrieval can produce robust changes in the same activity correlation measures used to define networks via resting-state fMRI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different cognitive processes also influence both the activation and connectivity of the DMN during resting-state scanning (Bellana, et al, 2017; Benjamin, et al, 2010; Chou, et al, 2017; Demertzi, et al, 2011; Van Calster, et al, 2016; Yan, et al, 2009). Although task-based fMRI has indicated that DMN regions increase in activity for episodic memory and internally driven mentalizing tasks (Buckner, et al, 2008), our findings suggest that relatively long bouts of minimally guided autobiographical retrieval can produce robust changes in the same activity correlation measures used to define networks via resting-state fMRI.…”
Section: Discussionmentioning
confidence: 99%
“…Bellana, et al (2017) compared autobiographical retrieval versus resting states specifically in the DMN. They found that DMN similarity across autobiographical retrieval and rest accounted for about 42% of the variance of this network, indicating that while there is some stability, a great deal of variability in connectivity exists between these states.…”
Section: Introductionmentioning
confidence: 99%
“…Related evidence reveals differences in functional connectivity among regions within the default network during episodic remembering and future imagining (48) and indicates that some default network regions (i.e., parahippocampal and retrosplenial cortices) show increased activity during episodic remembering relative to future imagining, likely reflecting enhanced contextual processing for the former compared with the latter (49). …”
Section: Neural Mechanismsmentioning
confidence: 99%
“…The "default mode network", a regional brain interlocking nexus distinct from other networks, represents a confluence of interacting brain regions, expressing more-or-less synchronically correlated activity, and pathways under activation at times when individuals are unfocused upon the surrounding environment and their brains remain in a state of wakeful rest (Bellana et al, 2016) [14]. It has been found that abnormalities in the intrinsic activity of resting state networks may contribute to the etiology of conduct disorder and poor prognosis of ADHD in combination with conduct disorder (Uytun et al, 2016) [15]; whereas reduced default mode functional connectivity is associated with expressions of conduct disorder (Broulidakis et al, 2016) [16], individuals presenting ADHD present disproportionately high expressions of default mode network activity related to goal-directed tasks accompanied by 'switch-specificity alterations in the right insula region (Sidlauskaite et al, 2016) [17].…”
mentioning
confidence: 99%